Efforts and Effectiveness in Improving Knowledge and Skills of Vocational Assessment for Teachers Supporting Career Decisions of Students with Intellectual Disabilities - Imai, Aya; Maebara, Kazuaki; Yaeda, Jun (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
Background: The number of options available to people with disabilities has gradually increased in Japan. At educational institutions where students with disabilities are enrolled, teachers must understand the various ways of life and provide appropriate guidance and support based on the actual conditions of individual students so that students can independently choose their career paths through self-selection and self-determination. Objective: This study aimed to examine the effect of an intervention using a vocational assessment training program on eight teachers at a special needs school in Japan. Methods: The level of knowledge and skills was assessed before and after the intervention. Intervention effects were analyzed through the Self-Assessment for Students and Counselors-Revised tool using the Wilcoxon signed-rank test, with corresponding samples for differences in mean scores before and after the intervention. In addition, the difference in the mean pre- and post-intervention scores for teachers with 10 or more years of upper secondary school experience (high experience group) and those with less than 10 years of upper secondary school experience (low experience group) was calculated. Principal Verdicts: Indicated that the training program intervention helped teachers recognize the importance of vocational assessment and subsequently improve their teaching. Furthermore, the number of years of experience in upper secondary schools influenced the effectiveness of the intervention. Conclusions: It was suggested that this training program would be effective for professionals who have acquired basic knowledge and skills in vocational rehabilitation.